DAMPAK PEMIKIRAN SAUSSURE BAGI PERKEMBANGAN LINGUISTIK DAN DISIPLIN ILMU LAINNYA - didi sukyadi (PAROLE: Journal of Linguistics and Education, 2013)
There is no discipline  standing alone. What we know and what we create  or  engineer  both  directly  and  indirectly  are  influenced  by other people’s ideas. Semiotics as a discipline just appearing at the beginning of the 20th century has flourished not only in linguistics and  literature,  but  also  in  other  disciplines  such  as  anthropology, sociology,  psychiatry,  culture,  music,  arhitecture,  advertisement, and  even  politics.  We  are  all  aware  that  all  these  embryos  derive from  Saussure’s  ideas    which  became  the  foundation  of structuralism  such  as  synchronic-diachronic,  language-parole, signifier-signified,  arbitrary-motivated,  and  syntagmatic- paradigmatic. This paper will elaborate Saussure’s essential ideas, and their impacts to the studies of linguistics, literature, and other disciplines as well as the development of semiotics today.Tidak  ada  ilmu  yang  berdiri  sendiri.  Apa  yang  kita  ketahui,  apa yang  kita  ciptakan atau  rekayasa secara  langsung  maupun  tidak langsung  dipengaruhi gagasan  atau  pikiran  orang  lain.  Semiotika sebagai sebuah disiplin ilmu yang baru muncul pada awal abad dua puluh  telah  berkembang  begitu  pesat  dan  luas  tidak  hanya  dalam linguistik dan sastra tetapi juga dalam disiplin ilmu lainnya seperti antropologi,  sosiologi,  psikiatri,  budaya,  musik,  arsitektur,  iklan, dan  bahkan  politik. Kita  menyadari  cikal-bakal  semua  itu  adalah gagasan  Saussure  yang  menjadi  dasar  strukturalisme  seperti synchronic-diachronic, langue-parole,  signifier-signified, arbitrary-motivated, dan syntagmatic-paradigmatic.  Tulisan  ini berusaha  memaparkan  buah  pikiran  penting  Saussure, dan dampaknya  bagi  kajian  linguistik,  sastra  dan  bidang  lainnya  serta perkembangan kajian tanda saat ini.